Population genetic structure and connectivity of the harmful dinoflagellate Alexandrium minutum in the Mediterranean Sea - Casabianca, Silvia (The Royal Society, 2012)
The toxin-producing microbial species Alexandrium minutum has a wide distribution in the Mediterranean Sea and causes high biomass blooms with consequences on the environment, human health and coastal-related economic activities. Comprehension of algal genetic differences and associated connectivity is fundamental to understand the geographical scale of adaptation and dispersal pathways of harmful microalgal species. In the present study, we combine A. minutum population genetic analyses based on microsatellites with indirect connectivity (C(i)) estimations derived from a general circulation model of the Mediterranean sea. Our results show that four major clusters of genetically homogeneous groups can be identified, loosely corresponding to four regional seas: Adriatic, Ionian, Tyrrhenian and Catalan. Each of the four clusters included a small fraction of mixed and allochthonous genotypes from other Mediterranean areas, but the assignment to one of the four clusters was sufficiently robust as proved by the high ancestry coefficient values displayed by most of the individuals (>84%). The population structure of A. minutum on this scale can be explained by microalgal dispersion following the main regional circulation patterns over successive generations. We hypothesize that limited connectivity among the A. minutum populations results in low gene flow but not in the erosion of variability within the population, as indicated by the high gene diversity values. This study represents a first and new integrated approach, combining both genetic and numerical methods, to characterize and interpret the population structure of a toxic microalgal species. This approach of characterizing genetic population structure and connectivity at a regional scale holds promise for the control and management of the harmful algal bloom events in the Mediterranean Sea.